Herschel-PACS photometry of the five major moons of Uranus - Detre, Örs Hunor; Müller, Thomas; Klaas, Ulrich; Marton, Gábor; Linz, Hendrik; Balog, Zoltan (Astronomy and astrophysics, 2020)
Aims. We aim to determine far-infrared fluxes at 70, 100, and 160 μm for the five major Uranus satellites, Titania, Oberon, Umbriel, Ariel, and Miranda. Our study is based on the available calibration observations at wavelengths taken with the PACS photometer aboard the Herschel Space Observatory.Methods. The bright image of Uranus was subtracted using a scaled Uranus point spread function (PSF) reference established from all maps of each wavelength in an iterative process removing the superimposed moons. The photometry of the satellites was performed using PSF photometry. Thermophysical models of the icy moons were fitted to the photometry of each measurement epoch and auxiliary data at shorter wavelengths.Results. The best-fit thermophysical models provide constraints for important properties of the moons, such as surface roughness and thermal inertia. We present the first thermal infrared radiometry longward of 50 μm for the four largest Uranian moons, Titania, Oberon, Umbriel, and Ariel, at epochs with equator-on illumination. Due to this inclination geometry, heat transport took place to the night side so that thermal inertia played a role, allowing us to constrain that parameter. Also, we found some indication for differences in the thermal properties of leading and trailing hemispheres. The total combined flux contribution of the four major moons relative to Uranus is 5.7 × 10−3, 4.8 × 10−3, and 3.4 × 10−3 at 70, 100, and 160 μm, respectively. We therefore precisely specify the systematic error of the Uranus flux by its moons when Uranus is used as a far-infrared prime flux calibrator. Miranda is considerably fainter and always close to Uranus, impeding reliable photometry.Conclusions. We successfully demonstrate an image processing technique for PACS photometer data that allows us to remove a bright central source and reconstruct point source fluxes on the order of 10−3 of the central source as close as ≈3 × the half width at half maximum of the PSF. We established improved thermophysical models of the five major Uranus satellites. Our derived thermal inertia values resemble those of trans-neptunian object (TNO) dwarf planets, Pluto and Haumea, more than those of smaller TNOs and Centaurs at heliocentric distances of about 30 AU.
Gesehen am 15.10.2020